A life less lonely: the state of the art in interventions to reduce loneliness in people with mental health problems - Mann, Farhana (Soc Psychiatry Psychiatr Epidemiol, 2017)
PURPOSE: There is growing evidence of significant harmful effects of loneliness. Relatively little work has focused on how best to reduce loneliness in people with mental health problems. We aim to present an overview of the current state of the art in loneliness interventions in people with mental health problems, identify relevant challenges, and highlight priorities for future research and implementation. METHODS: A scoping review of the published and grey literature was conducted, as well as discussions with relevant experts, to propose a broad classification system for types of interventions targeting loneliness. RESULTS: We categorised interventions as ‘direct’, targeting loneliness and related concepts in social relationships, and ‘indirect’ broader approaches to well-being that may impact on loneliness. We describe four broad groups of direct interventions: changing cognitions; social skills training and psychoeducation; supported socialisation or having a ‘socially-focused supporter’; and ‘wider community approaches’. The most promising emerging evidence appears to be in ‘changing cognitions’, but, as yet, no approaches have a robust evidence base. Challenges include who is best placed to offer the intervention, how to test such complex interventions, and the stigma surrounding loneliness. CONCLUSIONS: Development of clearly defined loneliness interventions, high-quality trials of effectiveness, and identifying which approaches work best for whom is required. Promising future approaches may include wider community initiatives and social prescribing. It is important to place loneliness and social relationships high on the wider public mental health and research agenda.